Spontaneous breaking of the lepton number and invisible majoron in a 3-3-1 model - Pires, CSD; da Silva, PSR (Springer, 2004)
In this work we implement the spontaneous breaking of lepton number in version II of the 3-3-1 models and study their phenomenological consequences. The main result of this work is that our majoron is invisible even though it belongs to a triplet representation by the 3-3-1 symmetry.